Thinking of plasticity in the musical composition: sculpting time, modeling listenings (Orfeu, 2020)
This paper will discuss some problems in musical composition that trouble the compositional practice of the author, and that stand out due to its operating modes in the continuity of a temporal flow. The problems were raised from some observations and reflections made by a researcher about his own practice as a composer, but they also were explored and questioned in several contexts that point to singular compositional ideas. Thus, through analysis of pieces of different composers in contrast with the researcher’s compositions, this paper contributes to thinking about some compositional problems such like the function of plastic transformations of objects and musical textures in their relations with time, seen both as flow and as an event.
Keywords: Music Composition; gesture; compositional problem; time